Past, present and future of the active solar distillation system: a comprehensive review. Issue 1 (31st December 2022) - Patel, Mit; Patel, Chetankumar; Panchal, Hitesh
Abstract : The solar distillation device helps in converting saline water into potable water using solar power. It is a simple and easy device to transform salt water into drinking water. Many scientists have attempted to boost electricity distillate production. Two primary variables that are accountable for distillery production are higher air quality and reduced internal crystal cap thickness. The paper presents an examination of active solar distillation. Finally, different sophisticated techniques have shown the potential of active solar distillation